Peningkatan Minat Belajar IPS Melalui Penerapan Strategi Scramble Dengan Media Visual Siswa Kelas IV SD Negeri 01 Bolong Tahun Ajaran 2015/2016 - Megawati, Ajeng Wahyu, Drs. H.Mulyadi Sri Kamulyan, M.Pd (2016)
Fourth grade social studies in elementary school 01 Bolong known that a class IV student interest in social studies is still low and has not mancapai prescribed standards of the school. Based on these problems need their learning innovations to improve students' interest in learning IPS. To overcome these problems, the strategies implemented by the visual media scramble on fourth grade social studies lesson Negeri 01 Bolong. The research objective of this class action to increase interest in social studies through the implementation of the strategy with visual media scramble on fourth grade students of SD Negeri 01 Bolong Academic Year 2015/2016. This type of research is the Classroom Action Research (PTK) model of Kurt Lewin with four stages, namely planning, action, observation, and reflection. The results showed that the interest in learning increases, initial conditions 40, 36%, the first cycle of the first meeting of 61, 71%, the first cycle of meetings II 69, 52%, second cycle of the first meeting of 78, 38%, second cycle of meetings II 84, 37% , Increased interest in learning also have an impact on student learning outcomes, the initial conditions complete learn at 57, 08, the first cycle of the first meeting of 67, 29, the first cycle of meetings II 74, 16, the second cycle of meeting the first 76, 25, the second cycle of meeting II 80. It can be concluded that through the implementation of strategies scramble with visual media can improve learning and student learning outcomes IPS classrooms IV 01 Bolong elementary School 2015-2016 school year. Keywords: Interest in Learning IPS, Scramble Strategy, Visual Media